2014
DOI: 10.1097/aap.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Paravertebral Block and Its Effects on Chronic Pain and Health-Related Quality of Life After Modified Radical Mastectomy

Abstract: There is no significant difference in the incidence or relative risk of chronic pain at 3 and 6 months after an MRM when TPVB is used in conjunction with GA. Nevertheless, patients who receive a TPVB report less severe chronic pain, exhibit fewer symptoms and signs of chronic pain, and also experience better physical and mental HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 18 publications
3
130
0
Order By: Relevance
“…39,40 In contrast, persistent postoperative pain often results from nociceptive communication from injured peripheral tissue to the central nervous system via afferent nerves in the immediate postoperative period, and it is this communication that peripheral nerve blocks dramatically attenuate. 30 Interestingly, a recently published randomized trial by Karmakar et al 41 with a protocol very similar to that of the current study reported a similar decrease in the incidence and intensity of chronic pain 6 months after mastectomy, but only for subjects who received both a single-injection paravertebral block and subsequent 72-h perineural infusion compared with no regional anesthetic/analgesic. However, no statistically significant difference was detected between the subjects with a single-injection paravertebral block and perineural local anesthetic infusion and those who received a single-injection block and placebo infusion (essentially the treatment groups of the current study).…”
Section: Persistent Postsurgical Painmentioning
confidence: 70%
“…39,40 In contrast, persistent postoperative pain often results from nociceptive communication from injured peripheral tissue to the central nervous system via afferent nerves in the immediate postoperative period, and it is this communication that peripheral nerve blocks dramatically attenuate. 30 Interestingly, a recently published randomized trial by Karmakar et al 41 with a protocol very similar to that of the current study reported a similar decrease in the incidence and intensity of chronic pain 6 months after mastectomy, but only for subjects who received both a single-injection paravertebral block and subsequent 72-h perineural infusion compared with no regional anesthetic/analgesic. However, no statistically significant difference was detected between the subjects with a single-injection paravertebral block and perineural local anesthetic infusion and those who received a single-injection block and placebo infusion (essentially the treatment groups of the current study).…”
Section: Persistent Postsurgical Painmentioning
confidence: 70%
“…84,90 In addition, 4 studies (only 2 of which were double-blind) demonstrated an improvement in pain incidence or characteristics at 1 to 12 postoperative months. 9,76,101,103 In summary, the literature supports PVB as an effective perioperative analgesic technique for breast surgery. Paravertebral block can also provide surgical anesthesia and may decrease nausea and vomiting, hospital stay, and chronic postsurgical pain.…”
Section: Paravertebral Blockmentioning
confidence: 96%
“…Specifically, thoracic paravertebral blocks (PVBs) promise a protective effect against PPP 5 ;but relevant trials 21,28,44,45,49,50,56 were decidedly mixed: 4 identified a protective effect, 28,44,45,49 whereas 3 found no benefit. 21,50,56 Underlying these conflicting results are methodological limitations that discount the CNP contribution to PPP and obvious PPP screening discrepancies. Investigators have relied on subjective reporting of PPP presence 45,50,56 or severity 21,28,44,49 excluding CNP screening tools 21,28,44,45,49,50,56 and sensory testing.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have relied on subjective reporting of PPP presence 45,50,56 or severity 21,28,44,49 excluding CNP screening tools 21,28,44,45,49,50,56 and sensory testing. 21,44,45,50 Therefore, the likelihood that investigating potential PVB protective effect has been biased by failure to incorporate CNP screening is arguable.…”
Section: Introductionmentioning
confidence: 99%